2016
DOI: 10.1093/fampra/cmw034
|View full text |Cite
|
Sign up to set email alerts
|

French general practitioners’ sense of isolation in the management of elderly cancer patients

Abstract: Improving the communication between GPs, oncologists and geriatric medicine seems to be one response to the isolation that GPs feel when caring for older people with cancer. At the primary care level, integration of GPs into the oncogeriatric network and the creation of a cancer care communication system in collaboration with the relevant hospital teams may be effective solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…GPs are often portrayed as if they were working solo with their palliative patients [ 15 ]; however, GPs often prefer to work in local palliative teams with nurses and other trusted care providers, if available [ 11 , 16 ]. Hierarchical doctor-nurse relationships might persist in such teams [ 17 ], but not always [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…GPs are often portrayed as if they were working solo with their palliative patients [ 15 ]; however, GPs often prefer to work in local palliative teams with nurses and other trusted care providers, if available [ 11 , 16 ]. Hierarchical doctor-nurse relationships might persist in such teams [ 17 ], but not always [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Deaf have difficulty accessing medical information including a communication barrier with the practitioner and a lack of education and interpreters [ 5 , 9 , 10 ]. In addition; difficulties of communications remain between general practitioners and oncologists [ 38 ]. Exams such as mammography and Papanicolau examination are not understood as well by the Deaf although they undergo these tests as often as people with hearing [ 10 , 26 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several qualitative studies have been published on patients' perceptions of their cancer management [29], their relationship with the healthcare team [30] and their interest in medical education [31,32]. Other studies have examined the perceptions of healthcare teams on their patients' treatment [33][34][35]. These studies revealed a number of factors leading to communication di culties between the patient, the oncologist and the GP.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The literature shows that GPs believe that there is room for improvement in their communication with oncologists [23,45]. Although deeply involved in the management of patients with cancer, GPs feel isolated at crucial moments of the illness, and when making decisions at these times [33]. Many studies [12,13,17,20,45] reported unsatisfactory communication between GPs and oncologists.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%